A revision of the tribe Planitorini van Achterberg (Hymenoptera, Braconidae, Euphorinae), with description of a new genus from Australia - van Achterberg, Cornelis (Zookeys, 2017)
Abstract. The tribe Planitorini van Achterberg (Hymenoptera: Braconidae: Euphorinae) is revised. One new genus Paramannokeraia gen. n. (type species: P. gibsoni sp. n.) and five new species from Australia are described and illustrated: Mannokeraia albipalpis van Achterberg, sp. n., M. nigrita van Achterberg, sp. n., M. punctata van Achterberg, sp. n., Paramannokeraia gibsoni van Achterberg & Quicke, sp. n. and P. juliae van Achterberg, sp. n. The tribe Mannokeraiini van Achterberg, 1995, is synonymized with the tribe Planitorini (syn. n.).